Education transformation in Muslim societies : a discourse of hope - Nasser, Ilham, 1963- (Advancing Education in Muslim Societies Ser., 2022)
"In Education Transformation in Muslim Societies, Muslim scholars from around the world offer multiple perspectives on using educational hope to stimulate change, dialogue, and transformation, from kindergarten to universities in Muslim communities. For instance, though progress has been made in Muslim societies on early education and girls' enrollment, it is not well documented; but by examining effective educational initiatives and analyzing how they work, educators, policymakers, and government officials can create catalysts for positive educational reform and transformation. By adopting strength-based educational discourse, contributors to Education Transformation in Muslim Societies reveal how critical the whole-person approach is when enriching the brain and the spirit and instilling hope back into the teaching and learning spaces of many Muslim societies and communities"--